2016
DOI: 10.1371/journal.pone.0162957
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Clinical Assessment of NT-proBNP as a Diagnostic Tool for Preeclampsia, Gestational Hypertension and Gestational Diabetes Mellitus

Abstract: Common complications of pregnancy include preeclampsia (PE), gestational hypertension (GH) and gestational diabetes mellitus (GDM). Hypertensive disorders (PE/GH) and GDM may result in greater maternal, fetal and neonatal morbidity and mortality. Women with PE/GH, one of the most common causes of heart burden in an obstetrical setting, present with elevated serum levels of BNP and NT-proBNP. The aim of this study was to shed more light on the role of NT-proBNP in pathophysiology of PE, GH and GDM. The study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…But the current findings were consistent with the ones from Sadlecki et al [50], who stated that even though usually BNP levels are higher in pregnant women than in nonpregnant ones, the subjects recruited in his study showed that levels of BNP were significantly higher in pregnant women with gestational hypertension than normotensive pregnant ones. Current findings were also in line with findings from Hamed et al [40], who revealed that BNP levels were significantly higher among hypertensive patients compared to control subjects.…”
Section: Discussionsupporting
confidence: 93%
“…But the current findings were consistent with the ones from Sadlecki et al [50], who stated that even though usually BNP levels are higher in pregnant women than in nonpregnant ones, the subjects recruited in his study showed that levels of BNP were significantly higher in pregnant women with gestational hypertension than normotensive pregnant ones. Current findings were also in line with findings from Hamed et al [40], who revealed that BNP levels were significantly higher among hypertensive patients compared to control subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Previous study showed that the cumulative incidence of type 2 diabetes mellitus was 6 weeks to 28 years in postpartum women with GDM ( 5 ). GDM has negative effects on future generations, including neonatal death ( 6 ), stillbirth ( 7 ), perinatal mortality ( 8 ), preeclampsia ( 9 ), large fetus ( 10 ), neonatal jaundice ( 11 ), low blood sugar ( 12 ), low calcium ( 13 ), and so on. However, the pathogenesis of GDM is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were subsequently implemented with evidence of diastolic LV dysfunction[ 18 20 ] and worse myocardial strain on speckle tracking echocardiograms[ 21 ]. Findings during pregnancy were more severe in early onset preeclampsia than in term preeclampsia[ 22 ] and paralleled by increases in plasma natriuretic peptide levels[ 17 , 18 , 23 ]. Postpartum persistence of these abnormalities as preclinical LV dysfunction or LV hypertrophy remains unclear.…”
Section: Introductionmentioning
confidence: 99%